Cost analysis of a nationwide typhoid conjugate vaccine campaign in Burkina Faso - Jean-Louis Koulidiati; Robert L. Zoma; Eric I. Nebié; Soumaila Yameogo; Christelle Neya Ouedraogo; Joël Arthur Kiendrébéogo; Frédéric Debellut (PLoS ONE, 2026)
Background In Burkina Faso, typhoid fever remains a major public health concern, particularly among children under 15. In January 2025, a nationwide campaign introduced the typhoid conjugate vaccine targeting children aged 9 months to 14 years. This study aimed to estimate the cost of typhoid conjugate vaccine delivery during the national campaign and to identify the main cost drivers across different administrative levels. Methods We conducted a retrospective cross-sectional costing study using a microcosting approach from the perspective of the Ministry of Health. We collected data from fifty health facilities, eight health districts, five health regions, and the national level. Financial and economic costs were estimated for each level, excluding vaccine and syringe costs. All costs were converted to 2024 USD using the official exchange rate. Parameter uncertainty was explored through one-way sensitivity analysis on key assumptions. Findings Vaccinators administered a total of 10.5 million typhoid conjugate vaccine doses. The average financial cost per dose was $0.47 (95% CI: $0.39–$0.51), and the economic cost was $2.16 (95% CI: $1.71–$2.56). Human resources and per diem payments were the main contributors to costs. Costs varied by geography, delivery strategy, and security context, with higher costs observed in rural and conflict-affected areas. The mobile–temporary posts strategy had the highest economic cost per dose ($2.02; 95% CI: $1.64–$2.40), while the fixed strategy had the highest financial cost per dose ($0.41; 95% CI: ($0.32–$0.49). Sensitivity analyses indicated robust cost estimates, with volunteer time valuation having the greatest influence. Conclusion The financial cost per dose remained within Gavi’s operational support range. The observed cost variations highlight the need for targeted funding and enhanced logistical support to ensure equitable access, particularly in rural and insecure areas. This study provides evidence to inform future vaccination campaigns and supports decision-making for typhoid conjugate vaccine introduction in other countries in the region.